Translation, validity, and reliability of an Arabic version of the short Healthy Eating Index tested in young Saudi adults: a questionnaire-based study - Alzaben, Abeer Salman; Bawazeer, Nahla Mohammed (Frontiers in Public Health, 2025)
IntroductionThe short Healthy Eating Index (sHEI) effectively evaluates overall and specific aspects of dietary quality; however, an Arabic version has not been developed yet. This study aimed to translate the sHEI into Arabic, adapt it culturally, and assess its reliability and validity among young Saudi adults.MethodsThe 22-item sHEI was translated and reviewed by a panel of nine Saudi nutritionists and dietitians for face and content validity. Reliability was assessed using an online, self-administered questionnaire completed by 615 participants recruited through convenience sampling. Internal consistency was evaluated with Cronbach’s alpha, and construct validity was assessed through factor analysis using Bartlett’s test of sphericity and the Kaiser–Meyer–Olkin measure of sampling adequacy.ResultsFace validity analysis indicated a 90% comprehensibility score, whereas content validity values for individual items ranged from 0.89 to 0.99, with a mean expert endorsement between 0.98 and 1.00. The sHEI nutrition scale achieved a Cronbach’s alpha of 0.81 for adequacy-related items after excluding Question 22 (water intake). Principal component analysis identified three factors related to adequacy and one factor related to moderation.DiscussionThe Arabic version of the sHEI demonstrated strong validity and reliability for assessing dietary quality among young Saudi adults. It provides a practical tool for use in community-based assessments, nutritional interventions, and future research.